FACTORS AFFECTING COMPLIANCE OF PREGNANT WOMEN IN CONSUMING IRON TABLETS (FE) AT THE INDEPENDENT PRACTICE OF MIDWIFE ISTIQOMAH, SIMPANG PADANG VILLAGE, BENGKALIS REGENCY - Kasmara, Dwi Pratiwi (JURNAL IBU DAN ANAK, 2024)
The maternal mortality rate in 2021 was 1,188 cases. Another cause of maternal death is complications of pregnancy, one of which is anemia. Anemia is a condition where the erythrocyte period or the circulating hemoglobin period cannot fulfill its function to transport oxygen to body tissues. to prevent anemia pregnant women are advised to take Fe tablets. The research design used is a Cross sectional study, aiming to determine the Factors That Affect Compliance of Pregnant Women Consuming Iron Tablets (FE) in the Independent Practice of Midwives Istiqomah Raheim Simpang Padang Village, Bengkalis Regency in 2022. The total sample was 75 people with total sampling technique. Data collection tools using questionnaires. In this study the data were analyzed univariately and bivariately with the Chi-Square Test. the relationship of knowledge of pregnant women with compliance with consuming iron tablets (Fe) with a p value = 0.004 (P < 0.05), There is no relationship between the age of pregnant women with compliance with consuming iron tablets (Fe) with a p value = 0.499(P >0.05), There is no relationship between parity of pregnant women and compliance with consuming iron tablets (Fe) with a p value = 0.617 (P > 0.05). There is no relationship between the pregnancy distance of pregnant women and adherence to consuming iron tablets (Fe) with a p value = 0.571 (P >0.05)